The climatic impact of food consumption in a representative sample of Irish adults and implications for food and nutrition policy - Hyland, John J; Henchion, Maeve; McCarthy, Mary; McCarthy, Sinéad N (Public health nutrition, 2017)
To evaluate the greenhouse gas emissions (GHGE) associated with the diet of Irish adults. GHGE were estimated by applying conversion factors to habitual food consumption data taken from the National Adult Nutrition Survey, which was representative of the population. Descriptive analyses were undertaken for GHGE for the total population, as well as accounting for energy misreporting and across categories of sociodemographic and socio-economic factors and tertiles of emissions. Republic of Ireland. Adults aged 18-87 years (n 1500). The GHGE derived from daily dietary intakes was estimated as 6·5 kg of CO2 equivalents (CO2eq) per person. Males, younger consumers, those with secondary education and student employment status were associated with significantly higher GHGE. Red meat was the highest contributor to GHGE with 1646 g CO2eq arising from a mean intake of 47 g/d. Dairy and starchy staples were the next largest dietary GHGE sources, with mean daily emissions of 732 g CO2eq and 647 g CO2eq, respectively. The lowest emissions were associated with consumption of vegetables, fruits and legumes/pulses/nuts. Based on profiling using actual food consumption data, it is evident that one single measure is not sufficient and a range of evidence-based mitigation measures with potential to lower emissions throughout the food chain should be considered. The research contributes towards an improved understanding of the climatic impact of the dietary intakes of Irish adults and can serve to inform a sustainability framework to guide action in food and nutrition policy development.